Association of follow-up neutrophil-lymphocyte ratio with postoperative pneumonia in aneurysmal subarachnoid hemorrhage patients after endovascular treatment: a retrospective analysis - Xinyue Huang; Xutang Jiang; Wen Gao; Wen Gao; Liming Guo; Xiumei Guo; Xiumei Guo; Hanlin Zheng; Zhigang Pan; Qingxin Lin; Shuni Zheng; Chuhan Ke; et al. (Frontiers in Medicine)
IntroductionResearch on the relationship between dynamic neutrophil-to-lymphocyte ratio (NLR)—measured at different time points around endovascular treatment—and the occurrence of postoperative pneumonia (POP) in patients with aneurysmal subarachnoid hemorrhage (aSAH) is still relatively scarce. This study aims to explore the association between dynamic NLR and the incidence of POP in patients with aSAH undergoing endovascular therapy.MethodsThis study included patients with aSAH who underwent endovascular treatment between January 2019 and April 2023. The follow-up endpoint was the presence of POP at 30 days postoperatively. Logistic regression analysis was conducted using POP as the dependent variable. The NLR was calculated at admission (NLR1), 24 h after endovascular treatment (NLR2), and 3–7 days after endovascular treatment (NLR3). Four prediction models were constructed: Model 1 (variables with p < 0.05, except for the NLR), Model 2 (Model 1 plus NLR1), Model 3 (Model 1 plus NLR2), and Model 4 (Model 1 plus NLR3).ResultsAmong the 154 patients with aSAH, POP occurred in 101 (65.6%) patients. Higher NLRs at admission [odds ratio (OR) = 1.08; 95% confidence interval (CI): 1.02, 1.16; p = 0.019], 24 h postoperatively (OR = 1.14; 95% CI = 1.05, 1.25; p = 0.005) and 3–7 days postoperatively (OR = 1.17; 95% CI = 1.02, 1.38; p = 0.04) were associated with the occurrence of POP.ConclusionFollow-up NLR may be associated with POP in patients with aSAH treated endovascularly. Elevated NLR at admission, 24 h postoperatively, and 3–7 days postoperatively correlated with a high risk for POP.